The smartphone as an instrument for blood pressure measurement - Pawłowski, Mariusz; Gąsior, Jakub S.; Dziedzic, Ewelina; Klepko, Tomasz; Dąbrowski, Marek (Medical Studies/Studia Medyczne, 2017)
Introduction: Number of population suffering from hypertension is increasing. So that, monitoring of this phenomenon should concentrate attention of medical industry, and receive high priority. One of the recommended procedure in hypertension treatment, and control is home blood pressure monitoring, which can be tested using smartphone application. Aim of the research : To evaluate the feasibility of a new blood pressure (BP) measurement tool – a smartphone application. Material and methods : The study included 50 subjects with the diagnosis of hypertension. Blood pressure measurement was tested in the following conditions: using a sphygmomanometer and using a smartphone by a specialist, and using a smartphone by the patient him/herself. The total number of results that differed from the measurement performed by the specialist by more than 5 mm Hg, and by 10% or more, was counted. Results: Mean results of systolic and diastolic BP did not differ significantly between measurements done by a specialist using a sphygmomanometer and those done using a smartphone application. There were 82% of results of systolic and 92% of diastolic BP that differed from Korotkoff sound technique in a range greater than 5 mm Hg and 36% in systolic and 86% in diastolic BP by 10% or more. Conclusions: The tested application should not yet be used for BP monitoring.